The high notes : a novel - Steel, Danielle (Delacorte Press, 2022)
Iris Cooper has been singing ever since she can remember, hitting the high notes like no one else. When she is twelve, her father convinces the owner of a bar in Lake City, Texas, to let her perform, and she stuns the audience. In the ensuing years, never staying anywhere for long, father and daughter move from one dusty town to the next, her passion for music growing every time she takes the mike in another roadhouse. But it is not an easy life for Iris with her father in charge and using her income to pay for gambling, women, and booze. When she starts to tour at age eighteen, she takes on a real manager. Yet he exploits her too, and the singers and musicians she tours with are really the only family she has. It is they who give Iris the courage to finally fly free, leave the tour, and follow her dreams. After years of enduring the hardships of the road, exploitation, and abuse to do what she loves, Iris's big chance comes as her talent soars. But at the top at last, Iris still has to fight every step of the way.